Intelligent Interactive Multimedia Systems and Services - Tsihrintzis, George A.; Damiani, Ernesto; Virvou, Maria (Smart Innovation, Systems and Technologies, 2010)
This volume contains the Proceedings of the 3nd International Symposium on Intelligent Interactive Multimedia Systems and Services (KES-IIMSS 2010). This third edition of the KES-IIMSS Symposium was jointly organized by the Department of Informatics of the University of Piraeus, Greece and the Department of Information Technologies of the University of Milan, Italy in conjunction KES International.